2011
DOI: 10.1108/09590551111183290
|View full text |Cite
|
Sign up to set email alerts
|

Exploring retail format choice among US males

Abstract: PurposeThe purpose of this paper is to explore retail format choice among male shoppers, using desired store attributes and shopping orientations as predictors of format choice.Design/methodology/approachMale shoppers in the USA (n=560) were surveyed via the internet. Multiple regression was used to evaluate the data.FindingsThe findings identify distinctive predictors of male patronage across several retail formats including department stores, discounters, category killers, dollar stores and internet only sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…According to Zulqarnain, Zafar and Shahzad (2015), consumers now consider a number of factors when choosing a retail store. Diverse store types or categories expose customers to a multiple of choices when choosing the store from where to make a purchase (Carpenter & Brosdahl, 2011). The active store choice decision is conceptualized as the challenge of choosing when and where to shop (Leszczyc, Peter, Sinha & Timmermans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zulqarnain, Zafar and Shahzad (2015), consumers now consider a number of factors when choosing a retail store. Diverse store types or categories expose customers to a multiple of choices when choosing the store from where to make a purchase (Carpenter & Brosdahl, 2011). The active store choice decision is conceptualized as the challenge of choosing when and where to shop (Leszczyc, Peter, Sinha & Timmermans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent research in shopping behaviour, concerned with the store choice for shopping, focuses on different research streams: some studies identified desired store attributes for consumers who prefer to shop in specific retail formats and/or specific patrons for a given format (Jayasankaraprasad 2014;Jayasankaraprasad and Aryasri 2011;Carpenter and Brosdahl 2011;Seock 2009;Baker et al 2002); several studies emphasize the relationship between retail store environment and the shoppers' satisfaction (Marques, Cardoso, and Palma 2013;Mártinez-Ruiz, Jiménez-Zarco, and Cascio 2011;Mártinez-Ruiz, Jiménez-Zarco, and Izquierdo-Yusta 2010), and other studies have explored the evolving competition through strategies based on pricing across different retail store formats (Zielke 2010;Gauri, Trivedi, and Grewal 2008), on the location (González-Benito, Muñoz-Gallego, and Kopalle 2005;Mendes and Cardoso 2006;Farhangmehr, Marques, and Silva 2000), on a set of logistics clues (Teller, Kotzab, and Grant 2012), or even in considering emotional and arousal aspects intrinsic to the customers (Yoon 2013;Kaltcheva and Weitz 2006).…”
Section: The Choice Of Store Formatmentioning
confidence: 99%
“…Reutterer and Teller (2009) identified the impact of consumers' behaviors and attributes to maximize their utility on store format choice. Carpenter and Brosdahl (2011) found the effect of sexual difference on the store format choice. These above studies, however, did not consider the existence of a competitor with different pricing format in the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, this research explores the effect of competitor's price change or promotion from the retailer's perspective. Prior research in marketing has tended to focus primarily on customer's perspective such as purchasing choice and behavior (Hoch, Drèze, & Purk, 1994; Reutterer & Teller, 2009), consumer's response (Carpenter & Brosdahl, 2011; Lal & Rao, 1997), customer's preference on the pick‐up locations (Glaeser, Fisher, & Xuanming, 2019), and perception of brands (Shankar & Bolton, 2004; Suri, Manchanda, & Lee, 2004). These customer's perspectives influence consumers to shop or choose a grocery store with different pricing formats.…”
Section: Introductionmentioning
confidence: 99%